Reproductive performances of triploid male and female Nile tilapia Oreochromis niloticus (Linnaeus, 1758) at different ages - ODANG CARMAN; AKHMAD TAUFIQ MUKTI; MUHAMMAD ZAIRIN JR.; ALIMUDDIN ALIMUDDIN (Society for Indonesian Biodiversity, 2023)
Abstract. Carman O, Mukti AT, Zairin JR M, Alimuddin. 2023. Reproductive performances of triploid male and female Nile tilapia Oreochromis niloticus (Linnaeus, 1758) at different ages. Biodiversitas 24: 4235-4242. Triploidization has been known as a chromosome set manipulation strategy to produce sterile fish. This study aimed to examine the reproductive and sterility performances of triploid male and female Nile tilapia Oreochromis niloticus (Linnaeus, 1758) at different ages. The triploidization process using heat shock of 41°C for four minutes at four Minutes After Fertilization (MAF) of the zygote old made the population of triploid tilapia. Two steps of fish rearing were conducted, namely indoor fish rearing and outdoor fish grow-out. Fish were reared in a controlled laboratory (indoor) at the Reproduction and Genetics Laboratory of Aquatic Organisms, Department of Aquaculture, Faculty of Fisheries and Marine Science, IPB University for four months, and then fish grow-out was performed in a controlled pond for two months. Reproductive performances such as Hepatosomatic Index (HSI), Gonadosomatic Index (GSI), gonadal development, and sterility of triploid and diploid for both male and female tilapias were analyzed. These results showed that triploid tilapia generally indicated late gonadal development and growth compared to diploids before and during maturation. Triploid female tilapia showed a lower HSI than diploid female tilapia (P<0.05). Otherwise, triploid and diploid males showed the same HSI. GSI of triploid males and females were lower than diploid males and females (P<0.05) at every age, namely three-, four-, five- and six-month-old fish. Based on the size and histology of the gonad, triploid male and female tilapias showed sterile characteristics with gametogenesis inhibition.